Male and female collegiate ice hockey athletes` body composition over competitive seasons - Dengel, D. R.; Roelofs, E. J.; Czeck, M. A.; Bosch, T. A. (International Journal of Sports Medicine, 2021)
Eighty-three male and female (49/34) athletes underwent determination of total fat mass (FM), lean mass (LM), bone mineral density (BMD) and visceral adipose tissue (VAT) by dual X-ray absorptiometry during the pre-season, in-season and off-season. Athletes were classified by position of Goalie (G; M/F=7/6), Forward (F; M/F=26/18), or Defenseman (D; M/F=16/10). In males, all positions were similar in weight, FM, LM, BMD and VAT. In females, F weighed less than D and G. FM and VAT was lower in F than D and G, but D was not different from G. LM was lower in F compared to D, but not G, with no differences between D and G. There were no differences in BMD between positions. There were no seasonal changes in males for body composition variables. In females, FM, LM and VAT decreased from pre-season to in-season, while BMD increased. From in-season to off-season, LM increased and BMD decreased. From off-season to pre-season, FM and VAT increased. In conclusion, there were no differences across position or seasonal changes in body composition in males. However, there were positional and seasonal changes in body composition in females, indicating possible differences in training regimens during the off-season compared to males.